Effects of Mitragynine from Mitragyna Speciosa Korth. Leaves on Working Memory in Mice - Apryani, Evhy (2011)
Repeated exposure to opiates can lead to deficits in cognitive function. A study in 2000 reported that opioid users have the risk for the brain damage. In the present study,we examined the working memory effects of mitragynine extracted from Mitragyna speciosa mature leaves using object location task and the motor activity in open field test. Mitragynine of the dose 5, 10 and 15 mg/kg were administered intraperitoneally (IP) to mice for 28 consecutive days and evaluated on day 28 after the last dose treatment. Scopolamine was used as the positive control drug. After the completion of behavioral study, mice were sacrificed and the brain was used to evaluate any changes in hippocampal morphology and in the expression of N-Methyl-D-aspartic Acid Receptors-1 (NMDAR1) by using immunohistochemical method. It was observed, that the administration of mitragynine significantly reduced the locomotor acitivity in open-field test compared with vehicle ( p < 0.05). Some studies have been reported an association between exploratory behavior to the level of cognitive function. in object location task, mitragynine treated mice did not show any significance discrimination between the object that had changed position than the object that had remain in a constant position (p > 0.05). The analysis of the results obtained indicated that mice with cognitive impairment will spend more time exploring the familiar object than the novel one. An absence of any difference in the exploration of the two objects during the second phase can be interpreted as a memory deficit. Histological study did not show any morphological changes but immunohistochemical study showed down-regulation in the expression of NMDAR1. Our results suggested that chronic administration of mitragynine may alter the cognitive behavioral function in mice, while preserving the brain morphology.